2018
DOI: 10.14419/ijet.v7i4.35.26276
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Bee Colony for Features Selection Optimization in Increasing T-Method Accuracy

Abstract: The study of prediction has drawn great interest in a wide range of field. T-Method which was developed specifically for prediction of the multidimensional case using historical data to develop its baseline model proved that making a prediction is possible even with limited sample size. The element of the signal to noise ratio (SNR) adopted into the T-Method strengthens its robustness. Orthogonal array (OA) in T-Method was used as features selection optimization in improving the analysis speed, cost and comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In [30], the authors applied a stepwise forward and backward selection procedure for this purpose which showed an increase in accuracy in many cases conducted [30]. e author of [31] suggested a Binary Artificial Bee Colony (BABC) algorithm, and the findings revealed that T-Method + BABC worked better than T-Method + OA in a particular case study conducted [31]. e most recent reported study by [32] has specifically addressed OA's downside and suggested Binary Particle Swarm Optimization (BPSO), which indicates an increase in accuracy for specific case studies [32].…”
Section: Taguchi's T-methods For the Feature Selection Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In [30], the authors applied a stepwise forward and backward selection procedure for this purpose which showed an increase in accuracy in many cases conducted [30]. e author of [31] suggested a Binary Artificial Bee Colony (BABC) algorithm, and the findings revealed that T-Method + BABC worked better than T-Method + OA in a particular case study conducted [31]. e most recent reported study by [32] has specifically addressed OA's downside and suggested Binary Particle Swarm Optimization (BPSO), which indicates an increase in accuracy for specific case studies [32].…”
Section: Taguchi's T-methods For the Feature Selection Optimizationmentioning
confidence: 99%
“…e previous research by [31,32] was further expanded in this study by proposing the other variant of binary ABC called Binary Bitwise ABC algorithms with proper generalization aspect been amended into it, which is the application of bootstrap cross-validation.…”
Section: Taguchi's T-methods For the Feature Selection Optimizationmentioning
confidence: 99%
“…Inoh [25] improved the method to define the unit space theory into T a and T b methods while [3], [4], [26][27][28][29] focused on improving the baseline model accuracy for outliers and abnormal case data. Harudin et al [10] is the only published work outside Japan currently that improved the variables selection optimization in the T-Method using ABC. The findings were concluded to be case-to-case dependent.…”
Section: Related Studiesmentioning
confidence: 99%
“…Up until recently, the element of OA in the MT-Method has been continuously enhanced with various machine-learning algorithm approaches. Unlike the MT-Method, enhancement of the OA element within the T-Method for variables optimization is still at an initial stage but Harudin et al [10] did enhance the OA in the T-Method with an artificial bee colony algorithm (ABC) and the results showed that T-Method+ABC performed better compared to T-Method+OA for the specific case study conducted. There are several other studies done with the same intention which are yet to be published but have been shared in several forums.…”
Section: Introductionmentioning
confidence: 99%
“…The BBA belongs to the swarm intelligence-based along with particle swarm optimization (PSO), ant colony optimization, honey bee swarm optimization algorithm, cuckoo search optimization, and many others. Specifically, in optimizing the Tmethod prediction accuracy, Harudin et al [13] successfully employed the artificial bee colony algorithm for feature selection optimization. The result shows an improvement in prediction accuracy as compared to the conventional OA approach.…”
Section: Introductionmentioning
confidence: 99%